From trials to clinical practice: Temporal trends in the coverage of specialized allied health services for Parkinson's disease. (2nd December 2020) - Bloem, Bastiaan R.; Eimers, Marietta; van Galen, Mirte S.; Munneke, Marten; Darweesh, Sirwan K. L.
Abstract: Background and purpose: To determine how the coverage of specialized allied health services for patients with Parkinson's disease (PD) has developed in the Netherlands since the publication of trials that demonstrated cost‐effectiveness. Methods: We used healthcare expenditure‐based data on all insured individuals in the Netherlands to determine the annual proportion of patients with PD who received either specialized or generic allied health services (physiotherapy, occupational therapy, speech–language therapy) in 2 calendar years separated by a 5‐year interval (2012 and 2017). Specialized allied health services were delivered through the ParkinsonNet approach, which encompassed professional training and concentration of care among specifically trained professionals. Results: Between 2012 and 2017, there was an increase in the number of patients with any physiotherapy (from 17, 843 [62% of all patients with PD that year] to 22, 282 [68%]), speech–language therapy (from 2171 [8%] to 3378 [10%]), and occupational therapy (from 2813 [10%] to 5939 [18%]). Among therapy‐requiring patients, the percentage who were treated by a specialized therapist rose substantially for physiotherapy (from 36% in 2012 to 62% in 2017; χ 2  = 2460.2; p  < 0.001), speech–language therapy (from 59% to 85%; χ 2  = 445.4; p  < 0.001), and occupational therapy (from 61% to 77%; χ 2  = 231.6; p  < 0.001). By contrast, the number of patients with generic therapists did not change meaningfully. By 2017, specialized care delivery had extended to regions that had been poorly covered in 2012, essentially achieving nationwide coverage. Conclusions: Following the publication of positive trials, specialized allied healthcare delivery was successfully scaled for patients with PD in the Netherlands, potentially serving as a template for other healthcare innovations for patients with PD elsewhere. Abstract : Following the publication of positive trials, the ParkinsonNet approach was successfully introduced on a nationwide scale in the Netherlands as a cost‐effective intervention for people with Parkinson's disease. The successful wide‐scale implementation of specialized allied healthcare delivery may serve as a template for other healthcare innovations for patients with Parkinson's disease elsewhere.